Penalaran Matematis Siswa dalam Menyelesaikan Masalah Realistik Ditinjau dari Kemampuan Matematika - Nur Hanifah; Pradnyo Wijayanti (MATHEdunesa, 2026)
Mathematical reasoning is the process of thinking in drawing logical conclusions regarding mathematical problems based on statements that are proven to be true and known previously. This research is a descriptive study with a qualitative approach which aims to describe the mathematical reasoning of students who have high, medium and low mathematical abilities in solving realistic problems. The research subjects were 3 class VII junior high school students in Surabaya who represented each category of mathematical ability. The instruments used are mathematical ability tests, mathematical reasoning tests, and interviews. The research results show that students with high and moderate mathematical abilities analyze problems by identifying important information in the problem, proposing conjectures using assumptions based on important information in the problem, and constructing arguments by carrying out detailed calculations on the problem given. In drawing logical conclusions, students with high mathematical abilities draw conclusions based on the completion steps that have been carried out, while students with moderate mathematical abilities draw conclusions based on assumptions and completion steps that have been carried out. Students with low mathematical abilities analyze problems by identifying important information in the problem, put forward conjectures regarding the solution steps taken but do not explain the reasons for choosing the assumptions made, and experience difficulty in constructing arguments because the solution steps are not appropriate so they do not provide accurate conclusions. regarding the correctness of the solution.